Islamic Spectrum in Java: By Timothy Daniels, Surrey, UK: Ashgate, 2009. hbk. 210 pages (American Journal of Islam and Society, 2011)
Timothy Daniels’ Islamic Spectrum in Java critically examines the myriadof ways in which Javanese Muslims draw on religious and secular ideas toproject desirable futures for their local societies, for the Indonesian nation,and for Indonesia’s place in the global economic, political, and culturalstructures of the twenty-first century. This book identifies a broad rangeof desirable futures projected by Javanese Muslims, as well as a range ofbeliefs and practices that comprise Javanese Islam (12). While this engagingwork is very likely to appeal to scholars in many fields, theoreticallyand methodologically it is foremost an anthropological study. Synthesizingsymbolic and cognitive anthropology in order to “provide ‘thick description’1 symbols . . . and to ascertain the social distribution of knowledgeand formation of mental representations in various contexts (4).” Danielsdraws primarily on ethnographic fieldwork conducted in the Yogyakartaarea of south-central Java from 2003 to 2004 ...